P139 Co-morbid insomnia and sleep apnoea (COMISA): Identifying patients that are responsive to continuous positive airway pressure therapy. (7th October 2021) - Sweetman, A; Lack, L; Smith, S; Chai-Coetzer, C; Catcheside, P; Antic, N; Douglas, J; O'Grady, M; Dunn, N; Robinson, J; Paul, D; McEvoy, D
Abstract: Introduction: Co-morbid insomnia and sleep apnoea (COMISA) is a prevalent and debilitating condition that is difficult to treat. COMISA patients have lower average adherence to continuous positive airway pressure (CPAP) therapy compared to patients with sleep apnoea alone. However, a sub-sample of COMISA patients may show adequate CPAP use that improves both the insomnia and sleep apnoea. It is important to identify this group of CPAP-responsive COMISA patients to guide personalised-medicine approaches. Methods: Seventy-three COMISA patients (AHI≥15; ICSD-3 insomnia; 55% male, Age M=57y) completed questionnaires, home-based polysomnography, and one-week sleep diaries before and 6-months after commencing CPAP therapy. No patients accessed CBTi. We investigated baseline predictors of CPAP adherence (min/night) and overall change in Insomnia Severity Index (ISI) scores during treatment. Results: Average CPAP adherence was 205 minutes/night (SD=153). 56% of patients used CPAP at least 4h/night. Average CPAP adherence was predicted by higher baseline AHI (r=0.39), arousal index (r=0.28), N1 sleep (r=0.32) and age (r=0.26), and lower N3 sleep (r=-0.28). The ISI decreased from baseline (17.9, CI=1.2) to 6-month follow-up (11.6, CI=1.3; p<0.001). There was a significant positive association between ISI reduction and CPAP use (r=0.31). 26% of patients reported an ISI<8 at 6-month follow-up. Conclusion: Approximately half of COMISA patients show CPAP adherence of ≥4h/night and one quarter experience insomnia remission with CPAP. CPAP use is positively associated with AHI, light sleep, and age at baseline, and reduction of insomnia severity during treatment. Future randomized controlled trials are required to confirm the results of this small un-controlled study.